2019
DOI: 10.3390/ijms20122925
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the 5-HT2C Receptor Agonist WAY-163909 on Serotonin and Dopamine Metabolism across the Rat Brain: A Quantitative and Qualitative Neurochemical Study

Abstract: The effects triggered by serotonin2C (5-hydroxytryptamin2C, 5-HT2C) receptor agonists in the brain are often subtle, and methodologies highlighting their widespread actions to account for their multiple modulatory influences on behaviors are still lacking. We report an extended analysis of a neurochemical database on monoamines obtained after the intraperitoneal administration of the preferential 5-HT2C receptor agonist WAY-163909 (0.3 and 3 mg/kg) in 29 distinct rat brain regions. We focused on the metabolite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 72 publications
2
12
0
Order By: Relevance
“…The study revealed the highest effects in the amygdala, hypothalamus, and the relationships between cortical areas and subcortical regions. Thus, these results further confirm that 5-HT 2C R activation exerts widespread effects in the brain ( Chagraoui et al, 2019 ; Whitestone et al, 2019 ; De Deurwaerdere et al, 2020a ) and suggests that the effects on NA and 5-HT systems play a role in lorcaserin effects.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…The study revealed the highest effects in the amygdala, hypothalamus, and the relationships between cortical areas and subcortical regions. Thus, these results further confirm that 5-HT 2C R activation exerts widespread effects in the brain ( Chagraoui et al, 2019 ; Whitestone et al, 2019 ; De Deurwaerdere et al, 2020a ) and suggests that the effects on NA and 5-HT systems play a role in lorcaserin effects.…”
Section: Discussionsupporting
confidence: 75%
“…The effects are more tangible with lorcaserin especially for NA for which WAY-163909 did not modify the tissue content in all these brain regions ( Chagraoui et al, 2019 ). Irrespective of the monoamine involved, the CE is the only brain region where neurochemical changes of monoamines have been found with the two agonists, and already at the lowest dose ( Chagraoui et al, 2019 ; Whitestone et al, 2019 ). This points out that one of the most critical 5-HT 2C R roles is modulating the amygdala activity ( Hackler et al, 2006 ; Moya et al, 2011 ; Regue et al, 2019 ; van de Wouw et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, we found reduced levels of a serotonin metabolite 5-HIAA and the 5-HIAA/serotonin ratios, as well as their increase at week 2 of stress. The 5-HIAA/serotonin ratio is common biomarker of CNS serotonergic activity, reflecting the activation of serotonergic neurons and their serotonin release, followed by its metabolization 65,66 . Interestingly, our findings also parallel reduced 5-HIAA in 15-day zebrafish CUS reported in a different study earlier 67 .…”
Section: Discussionmentioning
confidence: 99%
“…45 More contemporary preclinical studies, using tissue sampling method, described increased 5-HT concentration in the orbitofrontal cortex, motor cortex-2, as well as increased DA turnover in the medial orbitofrontal cortex, in direct response to administration of 5-HT 2C selective agonist. 47,48 In aggregate, literature instantiates a plausible explanation for impact of 5-HT 2C agonism on change in 5-HT and DA transmission (as well as their relative balance) in brain pathways and regions relevant for impulse control, Figure 5 Complex regulation of 5-HT projections to prefrontal cortex. 1.…”
Section: Mechanism Of Action Of Viloxazinementioning
confidence: 99%